About the diagnosis, prognosis and treatment of endometrial carcinoma - Cruz Muñóz, Héctor (2015)
The clinical diagnosis of endometrial carcinoma in its early stages is very difficult because neither the symptoms nor the objective examination of evidence provided sufficiently characteristic as to affirm with any certainty. The symptom that always makes think of a malignancy of the endometrium is the uterine bleeding occurs in a woman who is in the post-menopausal period, but this symptom is not any own way of endometrial carcinoma developed in this period of life. Indeed, in a study conducted at the University Gynecological Clinic (23) on 488 cases of postmenopausal genital bleeding, 265 cases were malignancy (54.5%) of whom 55 had an endometrial carcinoma, ie, only 11.2% of patients who consulted a postmenopausal genital bleeding had endometrial carcinoma.